2017
DOI: 10.1007/s00280-017-3500-9
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A1 genetic polymorphism is a promising predictor to improve chemotherapy effects in patients with metastatic breast cancer treated with docetaxel plus thiotepa vs. docetaxel plus capecitabine

Abstract: Overall, DT and DC result in similar clinical efficacy for MBC patients; however, efficacy for each therapy differs depending on CYP1A1*2C genotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Nie et al previously reported that the polymorphism of CYP1A1 has a linkage with clinical outcome of NSCLC patients treated with EGFR-TKI (Nie et al, 2011a;Nie et al, 2011b). Previous study also showed that CYP1A1 genetic polymorphism was a promising predictor to improve chemotherapy effects in patients with metastatic breast cancer (Zhou et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…Nie et al previously reported that the polymorphism of CYP1A1 has a linkage with clinical outcome of NSCLC patients treated with EGFR-TKI (Nie et al, 2011a;Nie et al, 2011b). Previous study also showed that CYP1A1 genetic polymorphism was a promising predictor to improve chemotherapy effects in patients with metastatic breast cancer (Zhou et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…Fourth, the associations observed in this study pertain to docetaxel administered in combination with cyclophosphamide and sometimes epirubicin, and not docetaxel monotherapy. Fifth, some SNPs were singled out based on findings from earlier studies that used other combinations of taxane-based chemotherapy [ 15 , 35 , 51 56 ]. As our study was based on routine clinical care data, our findings warrant confirmation in randomized clinical trials before genotyping can be used to guide taxane effectiveness in routine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that polymorphisms in drug-metabolising genes not only pose as a risk factor for malignancy but also can serve as a predictive marker for drug efficacy and targeted therapies [27,28]. In metastatic breast cancer, patients with the CYP1A1*2C gene variant responded better to a treatment regimen involving docetaxel and capecitabine compared to those with the homozygous wildtype (CYP1A1*1) genotype (AA) who experienced a better efficacy with a combination of docetaxel with thiotepa [29]. In early breast cancer, CYP1A2 rs762551 has been shown to be a potential predictive marker for patients treated with aromatase inhibitors paving the way towards individualised tailored assessment of therapy [30].…”
Section: Cyp1a1/a2mentioning
confidence: 99%
“…Prodrugs that are bioactivated by CYP1 enzymes can broadly be classified into four groups of agents and include flavonoids, benzothiazoles, stilbenes and alkylating agents [29]. Aminoflavone (NSC686288, Figure 3), a ligand of AhR, has been shown to selectively induce apoptosis in MCF-7 breast cancer cells by activating the transcription of CYP1A1 and CYP1B1 with functional activity confirmed using the ethoxyresorufin-O-deethylase (EROD) activity assay both in vitro and in xenograft models [31].…”
Section: Cyp1a1/a2mentioning
confidence: 99%